Enhanced electrical stability of thin film transistors based on nanocrystalline silicon films. (1st March 2023) - Xu, Hongyuan; Wan, Guangmiao; Mai, Jiaying; Jiang, Zhixiong; Liu, Bin; Zhang, Shengdong
Abstract: In this work, nanocrystalline silicon (nc-Si) films were achieved by using normally processing method of amorphous silica thin film transistors (a-Si TFTs), plasma enhanced chemical vapor deposition (PECVD). The effects of PECVD process parameters on the crystallization rate of nc-Si films were comprehensively studied and then an optimized nc-Si film has been achieved with a crystallinity of 50.87%. The electrical properties and stability of nc-Si TFTs are further investigated and compared with a-Si TFTs. The Δ V th of the nc-Si TFTs are 0.14 V and −3.32 V under positive bias-temperature-illumination stress (60 °C, 30 V, 6000 nit) and negative bias-temperature-illumination stress (60 °C, −30 V, 6000 nit) after 1 h, which are 1.96 V and −5.51 V for a-Si TFT, respectively. The result reveals better photo stability of nc-Si TFTs than a-Si TFTs which is attributed to fewer defect states in nc-Si films.